A Critical Assessment of Public Consultations on GMOs in the European Union. (1st May 2009) - Ahteensuu, Marko; Siipi, Helena
Abstract : The paper highlights shortcomings in the public consultation practices on the deliberate release and placing on the market of GMOs in the European Union and in one of its member countries, Finland. It is argued that current GMO consultation practices do not meet the aims and objectives on which their introduction is typically justified. Specifically, they do not serve democracy, increase consensus, enable better decisions to be made, or establish trust. We conclude that there is a clear need for the active development of the GMO consultation practices and for a further critical discussion on the ethical and socio-political foundation of public engagement.